Pt-based nanoparticles decorated by phosphorus-doped CuWO4 to enhance methanol oxidation activity. (4th June 2021) - Wu, Taichun; Gan, Mengyu; Ma, Li; Wei, Shuang; Fu, Qinglan; Yang, Yanling; Li, TingTing; Xie, Fei; Zhan, Wang; Zhong, Xiujuan
Abstract : DMFCs are promising power storage devices, while for methanol oxidation reaction, weak catalysis and carbon monoxide poisoning greatly limit their wide commercialization, so it's greatly necessary to exploit the anode catalysts with high performance. Abstract : Direct methanol fuel cells are high-efficiency power storage equipment, while for methanol oxidation reaction, weak catalysis and carbon monoxide poisoning make them unsuitable for wide commercialization. In this study, we synthesized a phosphorus-doped CuWO4 carbon nanocomposite as a Pt-based co-catalyst (Pt–C/P–CuWO4 ) by hydrothermal, low-temperature phosphating and NaBH4 reduction methods. The nanocomposite has enriched surface area and active sites of Pt–C/P–CuWO4, and the involved electrochemical tests have indicated that Pt–C/P–CuWO4 exhibits excellent catalytic activity (1422 mA mgPt −1 ) towards methanol oxidation in an acid solution, exhibiting 1.43, 1.50 and 4.17 times better catalytic activity than Pt/C–CuWO4 (994 mA mgPt −1 ), Pt–C/P–CuO (920 mA mgPt −1 ), and Pt/C–H (341 mA mgPt −1 ), respectively. Noticeably, the Pt–C/P–CuWO4 catalyst demonstrates optimal tolerance in anti-poisoning, and has an initial potential of 0.15 V lower than that of Pt/C–H. This excellent catalytic activity can be imputable to the doping of phosphorus, which enhanced the conductivity and regulated the electronic structure of the bimetallic oxide, thus enhancing the interactions between the carrier and Pt, and is conducive to the formation of small-sized Pt nanoparticles. Therefore, the construction of phosphorus-doped CuWO4 carbon nanocomposites may provide an alternative approach to the exploitation of other excellent electrocatalysts.